Peran Keterampilan Dasar Mengajar Dalam Meningkatkan Kualitas Pembelajaran di Pendidikan Anak Usia Dini - Fauziah Nasution; Khoilula Hanum Tanjung; Annisa Hadisti Rahayu; Intan Puspita Sari; Nisafira Yulianti (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Early childhood education is the initial stage in forming a strong educational foundation for children. At this stage, the quality of learning is very important in developing children's potential optimally. One of the factors that play an important role in improving the quality of learning in early childhood education is the basic teaching skills possessed by educators. This study aims to explore and analyze the role of basic teaching skills in improving the quality of learning in early childhood education. The research used a descriptive-analytical approach with literature analysis. This research is qualitative in nature, where we did not collect primary data through surveys or interviews. basic teaching skills have a significant role in improving the quality of learning in early childhood education. Teacher educators need to develop and strengthen their basic teaching skills through continuous training and professional development. Improving the quality of learning in early childhood education will have a positive impact on children's development and their preparation for the next stage of education